2015
DOI: 10.1007/s11427-015-4807-6
|View full text |Cite
|
Sign up to set email alerts
|

Site-1 protease cleavage site is important for the ER stress-induced activation of membrane-associated transcription factor bZIP28 in Arabidopsis

Abstract: Many sources of stress cause accumulation of unfolded or misfolded proteins in endoplasmic reticulum (ER), which elicits the unfolded protein response (UPR) to either promote cell survival or programmed cell death depending on different developmental context or stress severity. The Arabidopsis membrane-associated transcription factor, bZIP28, is the functional equivalent of mammalian ATF6, which relocates from the ER to the Golgi where it is proteolytically processed and released from the membrane to the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The recent study reported that the canonical S1P recognition site RRIL in bZIP28 is critical for the ER stressinduced activation of bZIP28 (Sun et al, 2015). This claim was based on their observation that the mutant version of bZIP28, in which the canonical S1P recognition site RRIL is changed to GGIL, was unable to restore the tunicamycinsensitive phenotype of bzip28 bzip60 double mutants and to activate the ER stress marker genes BiP3 and CNX1 (Sun et al, 2015). Because our experimental evidence in the present study shows that S1P is not involved in bZIP28 activation, the possibility for reconciliation is that RRIL ?…”
Section: Discussionmentioning
confidence: 99%
“…The recent study reported that the canonical S1P recognition site RRIL in bZIP28 is critical for the ER stressinduced activation of bZIP28 (Sun et al, 2015). This claim was based on their observation that the mutant version of bZIP28, in which the canonical S1P recognition site RRIL is changed to GGIL, was unable to restore the tunicamycinsensitive phenotype of bzip28 bzip60 double mutants and to activate the ER stress marker genes BiP3 and CNX1 (Sun et al, 2015). Because our experimental evidence in the present study shows that S1P is not involved in bZIP28 activation, the possibility for reconciliation is that RRIL ?…”
Section: Discussionmentioning
confidence: 99%
“…However, NAC089 and NAC062 are essentially tail‐anchored proteins while bZIP28 has a long C‐terminal tail that faces the ER lumen and contains ER retention and export signals. Unlike NAC089 and NAC062 the C‐terminal tail on bZIP28 contains a conserved S1P cleavage site that allows for its further proteolytic processing by S2P (Sun et al ., ). Taken together, these findings indicate that NAC089 and NC062 must be activated by ER stress through unknown mechanisms.…”
Section: Membrane‐associated Transcription Factors and Endoplasmic Rementioning
confidence: 97%
“…In the model plant Arabidopsis , UPR is mediated by several ER membrane‐associated basic leucine zipper (bZIP) transcription factors, for example AtbZIP28 and AtbZIP60 (Liu and Howell, ). When misfolded proteins are accumulated in ER, the transmembrane domain of AtbZIP28 is cleaved via intramembrane proteolysis by the Golgi‐resident protease site‐2 protease (S2P), and the activated AtbZIP28 relocates to the nucleus to up‐regulate downstream genes (Che et al , ; Gao et al , ; Liu et al , ; Liu et al , ; Sun et al , ; Tajima et al , ; Zhou et al , ). In contrast, activation of the ER membrane‐associated AtbZIP60 depends on unconventional mRNA splicing of At bZIP60 controlled by the ER‐localized Inositol‐requiring enzyme 1 (AtIRE1), and an open reading frame shift resulted from splicing leads to nuclear localization of AtbZIP60 (Deng et al , ; Moreno et al , ; Nagashima et al , ).…”
Section: Introductionmentioning
confidence: 99%